Langgam Batik dan Souvenir Tembung Kecamatan Percut Sei Tuan Kabupaten Deli Serdang Sumatera Utara - Mayora Mayora; Purnama Sari Simamora; Chairina Chairina (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2025)
This research aims to analyze the role of batik styles and tembung souvenirs from Percut Sei Tuan District, Deli Serdang Regency, North Sumatra, in developing local communities, especially in economic and cultural aspects. Batik with a typical regional style and tembung souvenirs are superior products that have the potential to increase people’s income and introduce local cultural riches. The method used in this research is a qualitative approach using observation techniques, interviews and content analysis of these craft products. The research results show that these two products have a positive impact on the community’s economy, especially through increasing the skills of local craftsmen and increasing tourist interest. Apart from that, batik products and tembung souvenirs help strengthen regional cultural identity and promote local uniqueness at a wider level. This research concludes that the development of batik style and tembung souvenirs has a strategic role in economic empowerment and cultural preservation in Percut Sei Tuan District.